SUN-610 Acquired Generalized Lipodystrophy: A Rare Side Effect of PD1-Inhibitor Therapy - Shah, Amy (J Endocr Soc, 2020)
Background:Program cell death-1 (PD1) inhibitors, such as nivolumab and pembrolizumab, have shown efficacy as adjuvant treatment for cancers, including melanoma, and their frequency of use is increasing. A potential, but rare, side effect of PD1-inhibitors is acquired generalized lipodystrophy (AGL), an immune-related adverse event characterized by loss of subcutaneous adipose tissue (SAT) and insulin resistance-associated complications. AGL can result in irreversible endocrinopathies, including diabetes. Clinical Case: A 60-year-old overweight female (BMI 29.2), with no related metabolic complications or medical history of autoimmune disorders, was treated with nivolumab (240mg IV q2 weeks) for 1 year for metastatic melanoma on her right arm (staged T4bN2a) that underwent wide local resection. She completed therapy with no complications or lab abnormalities.One-month post-treatment, she noticed rapid weight loss and facial atrophy. Within 3 months, she had a 58% weight loss withsignificant loss of SAT; insulin resistance and diabetes(impaired fasting glucose 201; A1c 9.2%);hepatic steatosis diagnosed by liver biopsy; hypertriglyceridemia (5,309 mg/dL,); and undetectable leptin levels. She also developed prominent forearm muscles and leg veins. GAD antibody was negative. The loss of SAT and rapid weight loss, physical exam findings, onset of diabetes, steatosis and hypertriglyceridemia—all closely following therapy with nivolumab—led to a diagnosis of nivolumab-associated AGL. In addition to treatment for hypertriglyceridemia, the patient was placed on multiple oral and parenteral antihyperglycemic medications, including metformin, SGLT2i, GLP-1, and DPP4, but all were discontinued due to side effects. Ultimately, her A1c increased to 12.4% and she was placed on basal/bolus therapy. Discussion: AGL is associated with an increased risk of lymphoma. Metreleptin, a recombinant analogue of human leptin, is approved for treatment of metabolic complications of AGL. Some instances of lymphoma in AGL have occurred while the patient was receiving metreleptin, but data is inconclusive as to whether development of lymphoma is a side effect of metreleptin.(Brown RJ, Chan JL, Jaffe ES, et al, 2016) We believe treatment with metreleptin would have benefited our patient, but she declined due to potential side effects, including lymphoma. Nine months after nivolomuab therapy, her melanoma is in remission but she still has lipodystrophic characteristics with insulin resistant diabetes. She is being treated with pioglitazone and multiple daily insulin injections but has not achieved euglycemia despite a total daily insulin dose of 2 u/kg. Of note, injecting insulin and use of a continuous glucose monitor have been a challenge given the lack of SAT. Although AGL resulting from PD1-inhibitor therapy is rare, it is a condition for which this patient will need life-long treatment.